2020
DOI: 10.1016/j.bbe.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep-segmentation of plantar pressure images incorporating fully convolutional neural networks

Abstract: Comfort shoe-last design relies on the key points of last curvature. Traditional plantar pressure image segmentation methods are limited to their local and global minimization issues. In this work, an improved fully convolutional networks (FCN) employing SegNet (SegNet+FCN 8s) is proposed. The algorithm design and operation are performed using the visual geometry group (VGG). The method has high efficiency for the segmentation in positive indices of global accuracy (0.8105), average accuracy (0.8015), and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…First, import the original measurement data of the female last (the data of the female last comes from empirical data); use the footprint method to form a relatively matching foot corresponding model. Then, the last is repaired and refined by manual experience, and a one-size shoe last is produced, which is usually completed by multiple shoe last designers [15][16]. After the mother last is completed, it is scanned in 3D and imported into the last body design software for meshing operation to provide basic data models for last body trimming, different shoe size expansion and contraction, paired custom processing, and mass production processing.…”
Section: Resultsmentioning
confidence: 99%
“…First, import the original measurement data of the female last (the data of the female last comes from empirical data); use the footprint method to form a relatively matching foot corresponding model. Then, the last is repaired and refined by manual experience, and a one-size shoe last is produced, which is usually completed by multiple shoe last designers [15][16]. After the mother last is completed, it is scanned in 3D and imported into the last body design software for meshing operation to provide basic data models for last body trimming, different shoe size expansion and contraction, paired custom processing, and mass production processing.…”
Section: Resultsmentioning
confidence: 99%
“…The talar leg joint is painful and has poor stability. There may be knee hyperextension in the early support phase, lack of strength in pedaling, and limb clearance obstacles in the swing phase [31]. In this deformity, the affected foot rotates inward at the ankle-the foot points down, facing inward and the sole.…”
Section: Figure1 the Experiments On Plantar Pressure Dataset Acquisimentioning
confidence: 99%
“…The convolutional neural network based recognition methods demonstrate unique advantages and powerful capabilities in recent years [9]- [11]. Wang et al [12] introduced a fully convolutional networks based plantar pressure image segmentation method, the SegNet is utilized as the backbone. In [12], the researcher also found that the plantar pressure image segmentation results have potential applications in improving the comfort of shoes.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [12] introduced a fully convolutional networks based plantar pressure image segmentation method, the SegNet is utilized as the backbone. In [12], the researcher also found that the plantar pressure image segmentation results have potential applications in improving the comfort of shoes. An AlexNet based plantar pressure image segmentation method is also proposed in [13], and the computation complexity of plantar pressure sensor datasets is decreased via the segmentation method.…”
Section: Introductionmentioning
confidence: 99%